A statistical approach for constructing an English-Chinese dictionary using a noisy parallel corpus. - Xu, Wenxiu. (2008)
This is a preliminary study of a statistical method for building an English-Chinese dictionary from manually paired corpus. The purpose is to match English documents with their relevance Chinese documents from unpaired corpora.